Predation by rainbow trout (Oncorhynchus mykiss) on a Western Australian icon: Marron (Cherax cainii) - Michelle Y. Tay; Alan J. Lymbery; Stephen J. Beatty; David L. Morgan (New Zealand Journal of Marine and Freshwater Research, 2007)
Considerable numbers of rainbow trout (Oncorhynchus mykiss) are captively produced then stocked into many wild aquatic systems in Western Australia despite a lack of understanding of their impact on the highly endemic native fish and freshwater crayfish of the region. The diet of an introduced, yet self‐sustaining population of O. mykiss was examined at Churchman Brook Reservoir in the Canning River Catchment, Western Australia, between September and November 2004. The large endemic freshwater crayfish marron (Cherax cainii) , which supports an iconic recreational fishery in Western Australia, comprised 61% by volume of all O. mykiss stomachs examined. The contribution made by C. cainii to the assimilated biomass of O. mykiss was confirmed by stable isotope analyses, which revealed that it dominated the assimilated diet of larger O. mykiss . The substantial contribution of C. cainii to the diet of wild O. mykiss suggests that, at least in habitat limited water bodies, it is likely to have a considerable predatory impact on C. cainii populations and may compromise some elements of this iconic recreational fishery.